Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


CosecA - cotA = root2 cotA (cosecA/cotA)-1=root2⇒equation1CosecA cotA = root2cotA                       =root2cotAfrom equation 1,                       =((cosecA/cotA)-1)cotA                = ((cotA×cosecA)/cotA)-cotA                                             =cosecA-cotA
hence proved

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts